Cyberbullying Among Adolescents in Norway: Time Trends and Factors Associated with Perpetration and Victimization - Tore Bonsaksen; Annette Løvheim Kleppang; Anne Mari Steigen (Behavioral Sciences)
There is limited knowledge about time trends in cyberbullying involvement, and whereas previous studies have often focused on various mental health outcomes, possible outcomes of cyberbullying may concern a wide range of areas. A better understanding of cyberbullying development over time, as well as of the possible consequences, is needed for effective prevention and intervention efforts. The aims of this study were (i) to gain knowledge of time trends in cyberbullying among Norwegian adolescents, and (ii) to better understand how different forms of cyberbullying involvement is related to a variety of outcomes. Data from the Norwegian Ungdata surveys (2014–2016) were used to assess involvement in cyberbullying over time. Associations with cyberbullying involvement and four outcome variables (belief in a good and happy life, loneliness, school thriving, and depressive symptoms) were assessed using logistic regression analyses. Across years of study, the prevalence rates for cyberbullying involvement were 1.5% for perpetration, 3% for victimization, and 1% for perpetration-victimization. Compared with non-involvement, involvement in cyberbullying in any role was associated with poorer outcomes on all variables. Cyber-victims who were also perpetrators were less likely to have high levels of loneliness and depressive symptoms, compared to cyber-victims only. The prevalence of cyberbullying involvement among adolescents in Norway was relatively unchanged between 2014 and 2016. Cyberbullying involvement is associated with negative outcomes related to mental health, loneliness, school thriving, and beliefs in one’s personal future, and victims of cyberbullying appear to be the most vulnerable group.